65 Years Retirement Age: Impact on Manual Workers and other Demanding Jobs. Supplementary Paper to the Final Report of the Pensions Working Group (Central Bank of Malta, 2005)
This report presents the findings of the reviews carried out on the participation of older workers in the labour force and on the impacts resulting from an increase in retirement age (to 65 years) on workers in manual and other demanding jobs. In accordance with the terms of reference, the report proposes a number of mitigation measures that may be adopted by Government to minimise any resulting negative impacts from increasing the retirement age to 65 years. The following is a synthesis of the findings. (...)
Keywords: 330